Upaya Pemenuhan Kebutuhan Istirahat Tidur Pada Ibu Post Partum - Abdullah, Anita Rizky; , Dr. Faizah Betty Rahayuningsih, A., S.Kep., M.Kes; , Winarsih Nur Ambarwati, S.Kep., Ns., ETN., M.Kep (2017)
Background. Spontaneous labor (normal delivery) is a process to pull out aterm conception product that consist of the baby itself, placental, amnion sac with head presentation (back of the head position), from uterus through birth canal ( either soft or rogged canal) with the power of mother itself (without any intervention from outside). After experiencing a tense and exhausting events. Mother who have labor need to get the best possible care especially in this periode (post partum). The Objective of the experiment is to occupy and maintain a rest full of sleep after normal labor in post partum periode to restourage enough energy for daily activities. The Author conduct result on fabruary 2017 in Gedongan Baki Sukaharjo. Method chosen by the author is observation, interview, and documentation. Result of the research find a disruption of sleep patterns assosiated with responsibility to provide infant care and anxiety because breast milk has not come out after delivery until the second days. Interventions, identification about sleep disosder and etiology of sleep disosder. Explain the medication aggaints the sleep pattern, discuss about technique of sleep pattern that can reduce anxiety, observation and note sleep requirment ofNy. S everyday. After 3 days of nursing intervention, disruption of sleep patterns have been solved, so the intervention need to terminated. The next plan of intervention is to provide support and motivation for her to get enough sleep and taking some rest. And also recommend Ny. S to preserve itensity of rest in order to maintain sleep patterns.